Analytical evaluation to the timber-concrete composite beam connected with notched connections. (15th January 2021) - Zhang, Lei; Zhang, Sigong; Chui, Ying Hei
Highlights: Analytical method is proposed for timber-concrete composite beam connected with notches. Both discrete and semi-rigid features of the connections are considered in the model. Internal actions in the beam can be solved from a group of linear equations. Discontinuous or non-smooth distribution of internal actions in the beam can be captured. Abstract: Timber-concrete composite (TCC) floor systems that combine the material merits of timber and concrete are gaining increasing interest from builders and designers around the world. The connections in the TCC system that marry timber and concrete together are the essential part that dominates the structural efficiency of the composite system. The most commonly used connectors such as steel fasteners are often closely spaced, which can be designed assuming continuous shear force transmission between timber and concrete. The notched connections in TCC systems are often widely and unequally spaced, thus shear forces are only transferred at discrete positions that should not be smeared along the entire beam. To determine the deflection, stress distribution, and relative slip between timber and concrete along the composite beam connected with notches, an analytical method with a simple release-and-restore procedure is proposed in this study. Both the discrete and semi-rigid features of the connectors are considered in the method. The proposed method is validated by comparing its predictions with those from other existing composite beam models and a finite element model through two examples. The discontinuous distribution of internal forces and stresses in the composite beam caused by discrete connections can be well captured by the proposed method. The proposed analytical procedure in this study can be used to facilitate the optimum design of TCC systems with discrete connection systems.